1997
DOI: 10.1089/jir.1997.17.377
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Evidence for a Novel Low Molecular Weight 2-5A-Dependent RNase L in Chronic Fatigue Syndrome

Abstract: Previous studies from this laboratory have demonstrated a statistically significant dysregulation in several key components of the 2',5'-oligoadenylate (2-5A) synthetase/RNase L and PKR antiviral pathways in chronic fatigue syndrome (CFS) (Suhadolnik et al. Clin Infect Dis 18, S96-104, 1994; Suhadolnik et al. In Vivo 8, 599-604, 1994). Two methodologies have been developed to further examine the upregulated RNase L activity in CFS. First, photoaffinity labeling of extracts of peripheral blood mononuclear cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(43 citation statements)
references
References 36 publications
(30 reference statements)
1
41
0
1
Order By: Relevance
“…Several reports indicated the up-regulation of components of the 2-5A/RNase L pathway in extracts of peripheral blood mononuclear cells (PBMCs) from CFS patients [145,146] as well as the accumulation of a low molecular weight 2-5A-binding protein of 37 kDa [147]. It has been proposed that this polypeptide could be a biochemical marker for CFS [148,149].…”
Section: ) Chronique Fatigue Syndrome (Cfs)mentioning
confidence: 99%
“…Several reports indicated the up-regulation of components of the 2-5A/RNase L pathway in extracts of peripheral blood mononuclear cells (PBMCs) from CFS patients [145,146] as well as the accumulation of a low molecular weight 2-5A-binding protein of 37 kDa [147]. It has been proposed that this polypeptide could be a biochemical marker for CFS [148,149].…”
Section: ) Chronique Fatigue Syndrome (Cfs)mentioning
confidence: 99%
“…Khalid Khabar showed that RNase L could affect the stability of PKR mRNA and levels of PKR, demonstrating that the two pathways are in a type of balance [56]. Studies by the groups of Robert Suhadolnik [57,58] and Bernard LeBleu [59,60] described up-regulation of the 2-5A system and accumulation of a 37 kDa polypeptide from RNase L in PBMC of patients with chronic fatigue syndrome. In addition, Lawrence Kuo's group at Merck Research Laboratories performed outstanding enzymology and biophysical studies of RNase L [61][62][63][64].…”
Section: Molecular Cloning Of Rnase Lmentioning
confidence: 99%
“…Previous studies from this laboratory (1) described structural similarities between two forms of 2Ј,5Ј-oligoadenylate (2-5A) 1 dependent RNase L in extracts of peripheral blood mononuclear cells (PBMC). The 2-5A-dependent 80-kDa RNase L is the terminal enzyme in the 2-5A synthetase/RNase L antiviral defense pathway (2).…”
mentioning
confidence: 99%